Rehabilitating Agriculture and Promoting Food Security After the 2010 Pakistan Floods: Insights from the South Asian Experience (The Pakistan Development Review, 2010)
The 2010 floods in Pakistan had a devastating effect on the Pakistani population. This paper summarises recovery experiences from previous natural disasters in South Asia, including the 2005 earthquake in Pakistan and the 1998 flood in Bangladesh, and suggests several lessons relevant for recovery efforts following the 2010 Pakistan flood. First, market and trade policies should maintain adequate price incentives so that private trade and imports can contribute to postdisaster recovery. Second, a strong institutional framework is needed to coordinate the large-scale disaster response. Third, recovery efforts should also include support for livelihood security and restoration, ensuring inclusion of the stakeholders. Fourth, restoring and upgrading infrastructure facilities can lead to enhanced flood resistance as well as a reduction in future disaster loss. Two alternative institutions may be possible vehicles for poverty-alleviation—the Pakistan Poverty Alleviation Fund (PPAF) and the Benazir Income Support Programme (BISP). To address future disasters, however, it is important to establish and strengthen disaster response capability, including applying lessons learned from the relief and rehabilitation response to the 2010 floods.